Comparison of road traffic injury characteristics between local versus floating migrant patients in a tertiary hospital between 2007 and 2010. - Chungui Xu (Public Library of Science (PLoS), 2014)
Background The aim of this study is to give a description of the road traffic injuries (RTIs) characteristics of floating migrant population by comparing with those of local residents in a harbor city of China. Methods A population-based descriptive study was carried out between 2007 and 2010 with RTI patient records from the Fifth Center Hospital of Tianjin. Inpatient diagnoses of RTI patients were defined using the International Classification of Diseases, Tenth Revision (ICD-10) codes. We analyzed the demographics and general characteristics of RTI patients that were in the hospital during the four years. In order to compare the group differences between local resident patients and floating migrant patients, the distribution of their ages, diagnoses, severity of injuries, duration of inpatient stays, hospitalization cost were analyzed. Results People between the ages of 16 and 55 were the most likely to suffer RTIs. The floating migrant patients between the ages of 16 and 45 had a higher incidence of accidents, while local resident patients between 46 and 55 had a higher incidence of accidents. Compared to local resident patients, floating migrant patients were more vulnerable to open injuries and severe traffic injuries. With the severity of injuries ranked from mild to severe, floating migrant patients had lower duration of inpatient stay, but higher hospitalization costs compared to local resident patients. Conclusions Floating migrant patients had a different age distribution, severity of injuries, diseases, inpatient duration and hospitalization cost compared with local resident patients. Compared to local resident patients, floating migrants had a higher risk to RTIs and were more vulnerable to severer traffic accidents at lower ages.